2020
DOI: 10.35381/r.k.v5i2.876
|View full text |Cite
|
Sign up to set email alerts
|

Prototipo de reconocimiento facial para mejorar el control de asistencia de estudiantes en UNIANDES, Quevedo

Abstract: La investigación tiene por objetivo diseñar un prototipo de reconocimiento facial para mejorar el control de asistencia de estudiantes en UNIANDES – Quevedo, para la identificación facial de los estudiantes al laboratorio de cómputo. El uso de este prototipo logró automatizar el proceso de registro de asistencia a clases de los docentes y estudiantes en los laboratorios de cómputo mediante el reconocimiento facial, facilitando esta tarea con rapidez y exactitud. El docente se coloca frente a la cámara que está… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…For a correct management of the teaching staff, every educational center must know the working time of all workers, the distribution of the different shifts within the educational center and the control of the time of entry and exit of each worker [9], which are data that must be managed efficiently, but currently it is observed that for the annotation of attendance of the teaching staff, it is necessary the supervision of a person who fills out the attendance record, existing a physical contact directly and leading to a possible contagion of COVID-19 [10], being able to form a new focus of contagion with all students, since this attendance control system that is used in educational centers are not optimal, they waste time in the registration process of each teacher forming a long queue, by some error the person who supervises can place some wrong information and in addition to wasting time in the process of searching for previous attendance records [11]. Therefore, our proposed system will allow the administrator to manage the information about the attendance of each teacher within the educational center just by viewing the report of the working days that the system will send automatically when the workers have registered their work attendance through a fingerprint reader that will recognize the identity of the teacher and through a user interface the teacher will confirm the data it shows.…”
Section: International Journal On Recent and Innovation Trends In Com...mentioning
confidence: 99%
“…For a correct management of the teaching staff, every educational center must know the working time of all workers, the distribution of the different shifts within the educational center and the control of the time of entry and exit of each worker [9], which are data that must be managed efficiently, but currently it is observed that for the annotation of attendance of the teaching staff, it is necessary the supervision of a person who fills out the attendance record, existing a physical contact directly and leading to a possible contagion of COVID-19 [10], being able to form a new focus of contagion with all students, since this attendance control system that is used in educational centers are not optimal, they waste time in the registration process of each teacher forming a long queue, by some error the person who supervises can place some wrong information and in addition to wasting time in the process of searching for previous attendance records [11]. Therefore, our proposed system will allow the administrator to manage the information about the attendance of each teacher within the educational center just by viewing the report of the working days that the system will send automatically when the workers have registered their work attendance through a fingerprint reader that will recognize the identity of the teacher and through a user interface the teacher will confirm the data it shows.…”
Section: International Journal On Recent and Innovation Trends In Com...mentioning
confidence: 99%
“…V Congreso Internacional en Inteligencia Ambiental, Ingeniería de Software, Salud Electrónica y Móvil adquirir imágenes en alta definición. Se utilizó MySQL como motor de la base de datos y se desarrolló un sitio web implementando HTML, CSS y JavaScript en el cual se podía acceder para la revisión del registro de asistencia [1]. En la Universidad del Norte (Colombia), División de Ingenierías, Departamento de Ingeniería Eléctrica y Electrónica se diseñó un sistema constituido por una interfaz Web y una red neuronal mediante el uso de Django y Python, la cual es capaz de permitir a un usuario poder ingresar fotos de un grupo cualquiera y poder generar, mediante reconocimiento facial, una lista de las personas que asistieron y no asistieron a dicha reunión del grupo [2].…”
Section: Introductionunclassified